The role of contract farming in the development of a competitive and sustainable cassava sub-sector in Vietnam - Wandschneider, T. (2013)
The role of Contract Farming in the Development of a Competitive and Sustainable Cassava Sub-sector in Vietnam. Tiago Wandschneider, Project Leader SADU-CIAT 8th Asian Cassava Research Workshop Vientiane, 20-24 October.